Doubled Haploid Technology in Maize (Zea mays): Status and Applications - GUPTA, MAMTA; CHOUDHARY, MUKESH; KUMAR, HARISH; KASWAN, VINEET; KAUR, YASHMEET; CHOUDHARY, JEET RAM; YADAV, SURESH (The Indian Journal of Agricultural Sciences, 2022)
Maize (Zea mays L.) is the third most important staple crop after rice and wheat with enormous diversity and adaptation ability. Hybrid breeding is the most important approach for developing high yielding cultivars in maize. It relies upon the generation of pure inbred lines with desirable traits in quick span to achieve higher genetic gains. Rapidly rising global population and climate change necessitates the development of innovative technologies that can help to safeguard the food security in future. Doubled Haploid (DH) technology is the best approach for rapid development of new inbred lines and has contributed immensely in the rapid generation of inbred lines and hybrid development. In addition, the use of molecular markers with DH technology resulted into mapping of genomic regions for different traits. The recent development in identification of alternative markers for haploid selection and genome editing approaches will further strengthen the DH technology for commercial maize breeding. This review describes important landmarks of maize DH technology, its applications, and recent advances in utilization of emerging technologies, viz. CRIPSR-cas and genomics approaches for DH technology